2009
DOI: 10.1149/1.3140022
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Chemically Synthesized FePt Nanoparticles

Abstract: L1 0 -FePt nanoparticle having high magnetic anisotropy is a promising candidate for the future ultra high magnetic recording material. We have succeeded in the fabrication of cubical FePt nanoparticles. It is necessary for high areal recording density to develop a homogeneous assembled technique of the cubical nanoparticle with its magnetic easy axis in the vertical direction on a substrate. It has been known the selective chemical reaction between metal species and functional group of organic molecules. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…4. Considering that the available literature on the binding of carboxylic ligands to monometallic and bimetallic NPs and surfaces reports the bridging bidentate as the preferred mode of interaction in most cases with the occasional dominance of the chelate biding, [71][72][73][74][75] it is likely that the proposed functionalisation mechanism, or certain aspects of it, are also applicable to those systems. The true mechanisms for the acid functionalisation of other metallic NPs are, however, subject to future research efforts.…”
Section: Functionalisation Mechanismmentioning
confidence: 99%
“…4. Considering that the available literature on the binding of carboxylic ligands to monometallic and bimetallic NPs and surfaces reports the bridging bidentate as the preferred mode of interaction in most cases with the occasional dominance of the chelate biding, [71][72][73][74][75] it is likely that the proposed functionalisation mechanism, or certain aspects of it, are also applicable to those systems. The true mechanisms for the acid functionalisation of other metallic NPs are, however, subject to future research efforts.…”
Section: Functionalisation Mechanismmentioning
confidence: 99%
“…For application as-synthesized FePt nanoparticles to BPM, we attempted to develop a simple process to control the distortion of the FePt array using chemical synthesis and geometrical grid prepared by ultraviolet nanoimprint lithography (UV-NIL). Previously, we succeeded in the fabrication of cubic FePt nanoparticles by controlling the reaction temperature in chemical synthesis; the FePt nanoparticles were immobilized by using chemical bonding on a thermal oxide Si substrate with modified (3-mercaptopropyl)trimethoxysilane, MPTMS as an interlayer between the FePt nanoparticles and the Si(100) substrate (14,15). The model image is shown in Fig.…”
Section: Uniformity Arrangement Of Fept Nanoparicles By Chemical Synt...mentioning
confidence: 99%
“…We have been investigating the nanoparticles of functional materials, 6 synthesized as a zero-dimensional system, often with focusing our attention on the application of their two-or three-dimensional assembly and/or dispersion with the use of their properties, e.g., magnetic nanoparticles for data storage, [28][29][30] catalytic nanoparticles for fuel cells, 31 and plasmonic nanoparticles for biosensing. 32 Design of the interface between nanoparticles and solution should contribute to the uniformity and quality of zero-dimensional building blocks and then control the functionality of their two-or three-dimensional assembly or dispersion.…”
Section: D Design For Nanoparticlesmentioning
confidence: 99%
“…Following to the achievement of controlled synthesis of FePt nanoparticles in view of interfacial design, 28,29 we are investigating the immobilization of nanoparticles with ordered orientation and arrangement, on the basis of design and control of the interface between FePt nanoparticles and SiO 2 /Si substrate by using the organosilane SAM formed from mercaptopropyltrimethpxysilane. 30 For Biomaterials Magnetite (Fe 3 O 4 ) nanoparticles have been attracting much interest because of their biocompatibility and wide use in medical and diagnostic applications such as magnetic resonance imaging, drug delivery system, cell separation, and hyperthermia. 33 It was demonstrated that the size of secondary particles, or aggregation of magnetite nanoparticles, as well as their surface charge affect the efficiency of their uptake into cells.…”
Section: For Magnetic Recording Devicesmentioning
confidence: 99%